Modelling the impact of condition-dependent responses and lipid-store availability on the consequences of disturbance in a cetacean - Burslem, Alec C.; Isojunno, Saana; Pirotta, Enrico; Miller, Patrick James (Conservation Physiology, 2022)
Funding: This work was supported by the United States Office of Naval Research (awards N00014-17-1-2757 and N00014-19-1-2479). Lipid-store body condition is fundamental to how animals cope with environmental fluctuations, including anthropogenic change. As it provides an energetic buffer, body condition is expected to influence risk-taking strategies, with both positive and negative relationships between body condition and risk-taking posited in the literature. Individuals in good condition may take more risks due to state-dependent safety (‘ability-based’ explanation), or alternatively fewer risks due to asset protection and reduced need to undertake risky foraging (‘needs-based’ explanation). Such state-dependent responses could drive non-linear impacts of anthropogenic activities through feedback between body condition and behavioural disturbance. Here, we present a simple bioenergetic model that explicitly incorporates hypothetical body condition-dependent response strategies for a cetacean, the sperm whale. The model considered the consequences of state-dependent foraging cessation and availability of wax ester (WE) lipids for calf provisioning and female survival. We found strikingly different consequences of disturbance depending on strategy and WE availability scenarios. Compared with the null strategy, where responses to disturbance were independent of body condition, the needs-based strategy mitigated predicted reductions in provisioning by 10%–13%, while the ability-based strategy exaggerated reductions by 63%–113%. Lower WE availability resulted in more extreme outcomes because energy stores were smaller relative to the daily energy balance. In the 0% availability scenario, while the needs-based strategy reduced deaths by 100%, the ability-based strategy increased them by 335% relative to null and by 56% relative to the same strategy under the 5%–6.7% WE availability scenario. These results highlight that state-dependent disturbance responses and energy store availability could substantially impact ...